Tourists’ Perspective on Ecotourism Destination Competitiveness: The Role of Tangible Components - Ching, Jia Lie; Lo, May Chiun; Mohamad Kadim, Suaidi; Abang Azlan, Mohamad; Chin, Chee Hua (HRMARS, 2019)
In this evolving digitalized ecosphere, ecotourism is one of the important catalysts in tourism and the government has been looking forward to the opportunities in promoting the uniqueness of ecotourism attraction through Visit Malaysia 2020 campaign. Moreover, the development of ecotourism destination should be implemented in a way that maximizes destination competitiveness. In our study, we examine the relationship between the tangible components of ecotourism destination competitiveness, namely, accessibility accommodation, cultural heritage, entertainment, infrastructure, natural resources, range of activities, and special events offered with ecotourism destination competitiveness, from the demand side point of view. A total of 225 respondents comprising tourists both international and domestic tourists visited Gunung Gading National Park in Sarawak, Malaysia took part voluntarily in this study. To assess the developed model, WarpPLS (version 6.0) was applied based on path modelling and then bootstrapping to generate the standard error of the estimate and p-values. Interestingly, the findings suggested that accessibility, natural resources, infrastructure and range of activities had a significant positive impact on ecotourism destination competitiveness, whereas no significant impact found among accommodation, cultural heritage, entertainment, and special events. Implications of these findings were further discussed.